Three models of democracy. On the concept of a deliberative policy (Polis (Santiago), 2018)
This paper seeks to compare the liberal and republican understanding of politics. Based on a critic of the type of renewal of "republicanism" that represents Frank Michelman, he develops a procedural concept of deliberative politics. He affirms that the crucial difference between the two approaches is the understanding of the role of the democratic process. Then explores the consequences of both approaches to the concepts of citizenship and law, noting that they represent a deeper disagreement about the nature of the political process.
Keywords: democracy; liberal conception; republican conception; citizen; right